Performance of the Linox implantable cardioverter defibrillator leads: A single‐center experience. Issue 12 (30th October 2019) - Marai, Ibrahim; Milman, Anat; Nof, Eyal; Gurevitz, Osnat; Barlev, David; Lipchenca, Igor; Bachar, Sharona; Glikson, Michael; Beinart, Roy
Abstract: Background: An early failure of Biotronik Linox implantable cardioverter defibrillator (ICD) leads has been reported from several centers. Aim: To compare the performance of Linox ICD leads with different other ICD leads as a report of the Sheba Medical Center experience. Methods: All patients who had implantation of Linox ICD leads between 2007 and 2016 were included in this study. ICD lead failure was defined as low‐ or high‐voltage impedance; failure to capture, sense, or defibrillate; or the presence of nonphysiological signals not due to external interference. The survival probability of Linox leads was determined and compared to Medtronic Sprint Quattro ICD leads. Results: A total of 340 patients (age 64.4 ± 1.8 years) were included in this analysis. They were followed up to 105 months (mean 45.7 ± 7, median 44 (Interquartile range (IQR) 26‐63) months). Twelve patients (3.5%) met the criteria for lead failure within 61.2 ± 22.9 months (median 66.5 [IQR 48–85 months]) post implantation. Noise with inappropriate ventricular arrhythmias detection, with or without therapy, was seen in 10 patients (83%). High pacing thresholds and high impedances were detected in two patients (17%). The survival probability of Linox leads at 60 months (97.3%) was similar to the survival probability of Sprint Quattro leads (98.2%) ( P = .58). Nevertheless, the survival probability at 105 months was much lower (81% vs 97%, Linox ICD lead and Sprint Quattro lead, respectively, P = .0039). Conclusion: Linox ICD leads have higher late failure rates compared to Sprint Quattro leads. These findings need to be confirmed in larger scale studies.